Phosphate removal and recovery as brushite by unseeded granulation in a fluidized-bed reactor - Caddarao, Patrick S. (College of Engineering, University of the Philippines Diliman, 2015)
The effects of influent phosphate pH, Ca+2:PO4-3 molar ratio, influent phosphate concentration, additions of commonly encountered ions in a TFT-LCD manufacturing plants such as fluoride (F-), sulfate (So4-2), and nitrate (NO3-); and the type of water used in the synthetic wastewater were investigated to maximize phosphate granulations and phosphate removal in an unseeded granulation in a fluidized-bed reactor. The solid phosphate granules collected after 60 h reaction time were identified as brushite (CaHPO4.2H20) by XRD. Experimental results showed that the highest phosphate removal of 97.58% was obtained at 1500 mg/L influent PO4 concentration, influent phosphate pH of 9 and Ca+2:PO4-3 molar ratio of 1.4:1.0. The largest brushite granules produced was greater than 1.00 mm. The addition of inorganic ions resulted in a slight decrease in phosphate removal of up to 5.33%. Effective granulation and high removal rates show that unseeded granulation of calcium phosphate using FBR could provide a foundation for phosphate removal and regeneration.